Optimal management strategies for promoting gestational extension in dichorionic diamniotic twin pregnancies - Chen, Caixia; Fan, Changyou; Wang, Bufei; Zhu, Ping (Frontiers in Physiology, 2024)
BackgroundPreterm birth is a significant concern in multiple pregnancies, warranting effective strategies to improve outcomes. Delaying delivery of the second fetus is crucial for reducing perinatal mortality rates.Case PresentationIn a dichorionic diamniotic twin pregnancy, one fetus experienced premature rupture of membranes (PROM) at 16+6 weeks gestation. Proactive fetal reduction through potassium chloride injection and emergency cervical cerclage at 19+1 week successfully extended the pregnancy to 39+5 weeks, resulting in a notable 160-day prolongation. Postoperative management encompassed comprehensive tocolytic therapy.ConclusionThe combined approach of proactive fetal reduction and emergency cervical cerclage proved successful in managing PROM in dichorionic diamniotic twin pregnancies. This innovative strategy offers a promising clinical solution for optimizing outcomes and prolonging gestation in high-risk multiple pregnancies, underscoring the importance of tailored interventions in complex obstetric scenarios.